2014
DOI: 10.1038/srep05863
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-cobalt bimetallic anode catalysts for direct urea fuel cell

Abstract: Nickel is an ideal non-noble metal anode catalyst for direct urea fuel cell (DUFC) due to its high activity. However, there exists a large overpotential toward urea electrooxidation. Herein, NiCo/C bimetallic nanoparticles were prepared with various Co contents (0, 10, 20, 30 and 40 wt%) to improve the activity. The best Co ratio was 10% in the aspect of cell performance, with a maximum power density of 1.57 mW cm−2 when 0.33 M urea was used as fuel, O2 as oxidant at 60°C. The effects of temperature and urea c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(100 citation statements)
references
References 28 publications
5
94
1
Order By: Relevance
“…However, the oxidation potential is also relatively higher, which could result in OER. On the other hand, the electrode with pure Co oxide exhibits the lowest current density, indicating that Co oxide has limited activity for the electrochemical oxidation of urea, which is consistent with other reports (Jiang and Fan, 2014;Kaushik, et al, 2008;Vedharathinam and Botte, 2013;Xu et al, 2014;Yan et al, 2012). Increasing Co content reduces the urea oxidation overpotential and simultaneously enhances the peak current.…”
Section: Electrochemical Characterization Of Ni X Co 3 à X O 4 /3d Grsupporting
confidence: 90%
“…However, the oxidation potential is also relatively higher, which could result in OER. On the other hand, the electrode with pure Co oxide exhibits the lowest current density, indicating that Co oxide has limited activity for the electrochemical oxidation of urea, which is consistent with other reports (Jiang and Fan, 2014;Kaushik, et al, 2008;Vedharathinam and Botte, 2013;Xu et al, 2014;Yan et al, 2012). Increasing Co content reduces the urea oxidation overpotential and simultaneously enhances the peak current.…”
Section: Electrochemical Characterization Of Ni X Co 3 à X O 4 /3d Grsupporting
confidence: 90%
“…7,44 In this section, we further investigated the activities of the Ni NP/NiFe LDH and NiFe LDH on urea oxidation reaction (UOR). From Fig.…”
Section: Fig 1 (As Well Asmentioning
confidence: 99%
“…The XRD pattern revealed that the ternary alloy deposited has a cubic crystalline structure since the peaks from the characteristic cubic planes of (111), (200), and (220) were observed at 2θ ≈ 44.0, 51.0, and 76.0, respectively, suggesting that the CuCoNi system is a solid solution [26,27]. In addition, the peaks located around 2θ ≈ (37.0, 42.0) and 55.0 are attributed to NiOx and Co(OH) 2 formation, respectively [27,28]. Figure 3 shows the CVs of (a) CNTs/GCE and (b-d) metal oxide modified CNTs/GCE in 1 M NaOH solution at a scan rate of 100 mV/s.…”
Section: Discussionmentioning
confidence: 98%